Religious Values in The Theme Structure of Traditional Seloko of Jambi Malay - Rahima, Ade; Ridwan, Sakura (IJLECR (International Journal of Language Education and Cultural Review), 2016)
The objective of this research is to get a deep understanding about religious values in the theme structure of traditional Seloko of Jambi Malay. This research used content analysis method to analyze the extrinsic elements of seloko containing religious values. This method was combined with hermeneutic study technique to reveal the structure and implicit meanings of the texts in Jambi Malay seloko. Data in this research are traditionalseloko containing religious values. Primary data were obtained from a collection of traditional seloko of Jambi Malay recorded by Lembaga Adat of Jambi Province. The results of this research show that the themes of traditional seloko of Jambi Malay are related to the religious values of man’s relationship with God, man with nature, man with society, and man with himself.